Aberrant Brain Activation During a Working Memory Task in Psychotic Major Depression. - Garrett, Amy; Kelly, Ryan; Gomez, Rowena; Keller, Jennifer; Schatzberg, Alan F.; Reiss, Allan L. (American Journal of Psychiatry, 2011)
Objective: The authors sought to better understand the neural circuitry associated with working memory deficits in psychotic major depression by examining brain function during an N-back task. Method: Study subjects were 16 patients with psychotic major depression, 15 patients with nonpsychotic major depression, and 19 healthy comparison subjects. Functional MRI data were collected while participants responded to letter stimuli that were repeated from the previous trial (1-back) or the one before that (2-back). Results: Relative to the healthy comparison group, both the psychotic and nonpsychotic major depression groups had significantly greater activation in the right parahippocampal gyrus during the 2-back task, and the psychotic major depression group showed this overactivation during the 1-back task as well. The nonpsychotic major depression group showed significantly lower activation than other groups in the right dorsolateral prefrontal cortex and greater activation than the healthy comparison group in the superior occipital cortex. The psychotic major depression group was unique in showing greater activation than both other groups in the right temporoparietal junction, a cluster that also demonstrated connectivity with activation in the left prefrontal cortex. Conclusions: The psychotic major depression group showed aberrant parahippocampal activation at a lower demand level than observed in nonpsychotic major depression. While the nonpsychotic major depression group showed abnormalities in frontal executive regions, the psychotic major depression group showed abnormalities in temporoparietal regions associated with orienting to unexpected stimuli. Considering the functional connectivity of this cluster with left dorsolateral prefrontal cortex regions, these findings may reflect neural compensation for sensory gating deficits in psychotic major depression. Reprinted by permission of the publisher.